(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
In modern production, each finished product entering the market is identified by a special marking. Each mark must meet requirements such as good coding, easy to see, easy to read by certain readers, stable over time, etc. In the present casting, laser marking of the C75 steel was carried out with a fiber laser with an average power of P = 30 W and a wavelength of λ = 1064 nm. For semi-contrast marking, marking speeds from 100 mm/s to 700 mm/s, average power from 10 to 30 W, raster pitch from 20 µm to 60 µm, scanning frequency from 20 kHz to 150 kHz were investigated as constant parameters are the pulse duration τ =100 ns, number of repetitions N = 1 and defocus Δ f = 0 mm. The influence of the changing parameters on the contrast was established, and experimental dependences were constructed. The achieved research results show that to obtain a high contrast mark, the average power should be above 20 W, the scanning speed up to 300 mm/s, the scanning frequency up to 50 kHz and the raster pitch up to 40 µm.